Piezoelectric properties of Pb0.985Sr0.01[(Zn 1/3Nb2/3)xTiyZrz]O 3 ceramics doped with 0.05 mol% Sb2O5 - P. Parjansri (2018)
Ceramic solid solutions within the system Pb0.985Sr0.01[(Zn1/3Nb2/3)xTiyZrz]O3doped with 0.05 mol% Sb2O5, where x = 0.02, 0.04, 0.06, 0.08 and 0.10, y = 0.46, 0.45, 0.44, 0.43 and 0.42 and z = 0.52, 0.51, 0.50, 0.49 and 0.48, were prepared by solid state reaction. The phase formation, microstructure, dielectric properties and piezoelectric properties of this system were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and electrical measurements. All compositions exhibit complete solid solutions of pure perovskite phases. The dielectric properties decrease with increasing content of the B1sites (Zn1/3Nb2/3)x. The maximum dielectric constant is about 25000. This observation suggests that the B-site substitution directly affects the dielectric properties, d33 constants and remanent polarization of this ceramic system. © 2009 American Institute of Physics.